PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. ALTRAK 1978 CABANG PEKANBARU - Hanifah, Nurul; ', Taufiqurrahman; Noviasari, Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of compensation and work environment on discipline of employees at PT. Altrak 1978 Branch Pekanbaru. As for the population in this study were employees of PT. Altrak 1978 Branch Pekanbaru 2015 as many as 87 people. Meanwhile, all the population are the respondent of this research, so the method is cencus. Analysis of the data using quantitative analysis tools that multiple linear regression with SPSS version 18.00. From the testing that has been done, simultaneous test (F-test) showed that compensation and work environment simultaneously have significant effect on the discipline of employees, while the partial test (t-test) showed that compensation and work environment partially significant effect on work discipline employee. Companies should pay more attention to discipline the employee to work with the maximum as leaders must have the courage to act decisively to apply penalties to subordinates who violate the rules. If there are employees who do not comply with work rules, the company reserves the right to give strict punishment for those employees. Sanctions here could be a suspension or dismissal of employees when the employee is no longer care for work discipline and reprimand from the boss.Keyword : Compensation, Work Environment and Discipline.